2007
DOI: 10.1007/s10815-007-9158-1
|View full text |Cite
|
Sign up to set email alerts
|

Retention of membrane charge attributes by cryopreserved-thawed sperm and zeta selection

Abstract: Purpose Mature sperm can be selected based on their negative zeta electrokinetic potential. The zeta selection of cryopreserved sperm is unknown. The objective was to study the effect of zeta processing on the morphology and kinematic parameters of cryopreserved-thawed sperm. Methods Colloid-washed sperm (N=9 cases) were cryopreserved for 24 h, thawed and diluted in serum-free medium in positive-charged tubes. After centrifugation, the tubes were decanted, serum-supplemented medium was added and the resuspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Thus, it is critical to select the most viable spermatozoa, and exclude the damaged cells following cryopreservation. Kam et al stressed the usage of zeta method in order to improve the selection of quality sperm after cryopreservation; however the technique is currently experimental [39]. In this study TEM, SEM and light microscopic examinations have shown that the rate of sperm cells having normal morphology decreased significantly.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, it is critical to select the most viable spermatozoa, and exclude the damaged cells following cryopreservation. Kam et al stressed the usage of zeta method in order to improve the selection of quality sperm after cryopreservation; however the technique is currently experimental [39]. In this study TEM, SEM and light microscopic examinations have shown that the rate of sperm cells having normal morphology decreased significantly.…”
Section: Discussionmentioning
confidence: 62%
“…Even though progressive motility declines after zeta selection on a cryopreserved sample, the selected sperm are more likely to have an intact acrosome and normal morphology. In one study, the markers of apoptosis and sperm necrosis were significantly reduced in a zeta selected sample [Kam et al 2007]. However, the recovery rate was only 8 to 10% of the original concentration used for cryopreservation.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…However, the recovery rate was only 8 to 10% of the original concentration used for cryopreservation. An adequate sperm concentration could not be obtained when sperm selection using zeta potential was used before cryopreservation [Kam et al 2007]. Because the recovery rate is low after zeta selection, it should not be used prior to cryopreservation.…”
Section: Zeta Potentialmentioning
confidence: 99%
“…Sperm membrane charge has been exploited by two other methods of sperm selection, Zeta test [22,23] and electrophoretic sperm separation [24,25]. Use of NCS selected by Zeta method resulted in an improvement in fertilization, implantation, and pregnancy rates [31,36], suggesting that selection of sperm with a high negative charge could aid in the isolation of mature and healthy sperm for ART.…”
Section: Discussionmentioning
confidence: 99%
“…Such sperm have higher net negative charge when compared with abnormal and immature sperm [18]. Selection of mature sperm based on differences in sperm membrane charge has been employed by two methods, the Zeta test [22,23] and electrophoretic sperm separation [24,25]. Sperm with high negative membrane charge have been shown to be morphologically normal, contain high protamine content [26] and have low levels of DNA damage [24,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%